Dichroism-sensitive photoacoustic imaging for in-depth estimation of the optic axis in fibrous tissue - Camilo Cano; Amir Gholampour; Marc van Sambeek; Richard Lopata; Min Wu (Photoacoustics)
Photoacoustic imaging (PAI) is a developing image modality that benefits from light–matter interaction and low acoustic attenuation to provide functional information on tissue composition at relatively large depths. Several studies have reported the potential of dichroism-sensitive photoacoustic (DS-PA) imaging to expand PAI capabilities by obtaining morphological information of tissue regarding anisotropy and predominant orientation. However, most of these studies have limited their analysis to superficial scanning of samples, where fluence effects are negligible. Herein, we present a mathematical model for the in-depth analysis of the DS-PA signal of biological samples, focusing on estimating tissue orientation. Our model is validated with a B-scan setup for DS-PA imaging in ex-vivo porcine tendon samples, for which collagen displays optical anisotropy. Results show that for in-depth DS-PA imaging, the accumulative fluence modulation due to dichroism overcomes the effect of absorption dichroism affecting the measured signals; however, this effect can be corrected based on the presented model for determining fiber orientation.